Formal Transformation in Urban Context Analytical Study to the Formal Transformation in Urban Context By using the remote sensing - Al-Hinkawi, Wahda Shuker; Haki, Maha Haki (Iraqi Journal of Architecture and Planning, 2009)
Many researchers interest directed to study the urban context as one of important concept to achieve temporal and spatial continuity in urban environment and link ihe buirding with neighboring. The paper deals with urban context as:- integral contain apposes crear orders and also statue procedurar definition it is contain of potential and outstanding orders which instituted fiom joined parts in urban fabric, linked together in potential relations and bear urban and cutturai values posses formal conduct, coinciding functiiinal and rotating and bear association deliberaiive meanings the potential in shared between the parte and the whole and the outstanaing in rorm"al properties and vision for elements which undergo for natural ani coactive transformation on the two dimensional and three dimeniional level, The outstanding order represents visual formal for urban contexl and the porential order represented in whole and partial syntax properties behind visible phenomena. The research confirm upon studying the transformation in formal properties within the urban context by subtract ideas, studies of translormation in formal properties on the level of the whole or part within the urban context, with this prospective t-he paper problem determined as: " There is no obvious conception about transformation nature in formal properties of urban context "- The paper hypothesis" the transformation in formal properties within the urban context at the level of whole causes the format transformation in properties at the level of parts, " was tested in real urban context represent by Ancient Damascus cit-v- in syria u, on. tf th. important urbanite and heritage element which has different type of .ont.it and it crouch to econorric ,society and physics conditions. The formal indicators was defined and measured b1’using (cls) techniques in dra*,ings and Analyzing visual and link formal properties on the level of the whole or part, the paper concluded that deforming transformation in urban context may cause the transflrmation in ihe context identity but it alio achieve formal homogeneity and prevenr the urban chaos, rvhen urban gradual growth and translormation md1 cause formal hetcrogeneity if building roles was not controlling the transformation process and organize the. the urban mix betwein old and new buildings.